Three-dimensional finite-difference time- domain modeling of road traffic noise - Gren, Max; Heiker, Staffan (My University, 2021)
With today’s rapid expansion and densification of urban areas, the amount of people living in close proximity to loud infrastructure on a daily basis is steadily increasing, which prompts a greater demand for control and prevention of traffic noise. Sufficiently detailed models of sound propagation in urban areas that are applicable to residential buildings are therefore in high demand and calls for further development. The aim of this study is therefore to design a three-dimensional Finite-Difference Time-Domain model for calculating and visualizing sound propagation in an outdoor environment, with the ability to implement both rigid and finite-mass objects for construction of building elements. Modeling of indoor sound pressure caused by an outdoor sound source is also a desired outcome. By establishing a model in Matlab, mainly consisting of sound pressure and velocity variables arranged in staggered grids, a foundation for performing a series of tests using noise screen and absorptive room models was established. The models were subsequently validated using analytical solutions for cases corresponding to the tests simulated in the model environment. The results from this study show that the rigid objects implemented in the model functioned properly with regards to the validating theoretical models, as well as the finite-mass wall and screen according to the mass law. Also, it was found that using artificial thick absorbing layers as sound absorbers functioned sufficiently well for simulating an acoustic environment appropriate for a residential room. Using the knowledge gained from this continuation of previous studies on the subject can serve as a useful tool for estimating traffic noise levels indoors, as well as a foundation for further development of the model and future studies of three-dimensional FDTD modeling of outdoor sound propagation.
Keywords: Traffic noise, three-dimensional, Finite-Difference Time-Domain; sound propagation, discretization, absorption, finite-mass